(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
SUMMARY: 1. Premise - 2. The recognition of the Autocephaly of the new Ukrainian Orthodox Church as a factor of crisis of relations between Ukraine and Russia - 3. The stages of the crisis - 4. The Kiev Metropolia of the Moscow Patriarchate and the War - 5. The Ukrainian Greek Catholic Church and the war. ABSTRACT: The paper analyzes the effects of the recognition of autocephaly by the new Ukrainian Orthodox Church. It constitutes one of the crisis factors in relations between Ukraine and Russia in the ongoing clash in the Orthodox Churches between the Ecumenical Patriarchate and the Russian Orthodox Church. The article reconstructs the positions of the various religious denominations present in Ukraine in contending for the representation of the interests of the Ukrainian people. It explores how the war is undermining the relationship between the Russian Orthodox Church and its Metropolia of Kiev. It also analyzes the role played in the crisis by the Ukrainian Greek Orthodox Catholic Church, a sui juris Church that aspires to play a supranational role.